LIFE CYCLE OF THE BLUE TIGER BUTTERFLY TIRUMALA LIMNIACE (LEPIDOPTERA: RHOPALOCERA: DANAIDAE) - S. APPALA NAIDU; S. P. VENKATA RAMANA (The Bioscan, 2010)
Tirumala limniace the blue tiger butterfly from India was studied in the environs of Eastern Ghats. It lays eggs singly on Wattakaka volubilis and this butterfly was seasonal in its distribution. The life cycle from egg to adult emergence is relatively shortest and spanning over 21-28 days. Besides, the population index of Tirumala limniace on same host plant leaves was discussed.